<전공 글쓰기>의 효율적 운용을 위한 전공별 수업모형 연구 - 계명대학교 ‘스포츠마케팅학과’ 사례를 중심으로 - 이은숙; 문동욱 (교양교육연구, 9(3), 2015)
본래 미국과 영국의 영향에서 출발한 <전공 글쓰기>는 신입생을 대상으로 하는 교양과정 글쓰기의 강의목표가 지나치게 광범위하고 막연하여 전공과목에서 요구하는 고유한 전공 관련 담론 방식을 익히는 데는 한계가 있다는 반성에서 출발하였다. <전공 글쓰기>의 필요성을 구체적으로 살펴보면 먼저, 글쓰기를 통해 전공 지식을 심화시키는 데 기여한다는 데서 생겨난다. 둘째, 전공 분야 담화의 특성을 익힘으로써 학술적 글쓰기를 할 수 있다는 것이다. 셋째, 이러한 능력은 전공인으로서 분명한 정체성을 확립하는 데 도움을 주어 졸업 후 전공과 관련한 취업을 하는 데 긍정적인 영향을 끼친다는 데서도 생겨난다. 넷째, 의사소통 능력을 필요로 하는 오늘날 <전공 글쓰기>를 통해 전공학습자는 전공인으로서 자기표현 능력 및 창의적 문제해결 능력, 그리고 융복합적 사고 능력을 배양할 수 있다는 것이다. <전공 글쓰기>가 지닌 이러한 장점을 활용하기 위해 계명대학교는 2013년 2학기부터 4개의 학과에서 <전공 글쓰기>를 개설하였으며, 2014년 2학기에는 28개의 학과에서 <전공 글쓰기>를 개설하였다. 이 글에서는 기획서 쓰기를 중심으로 하는 <스포츠마케팅>학과의 전공 글쓰기 사례를 살펴보면서 각 학과에 적절한 <전공 글쓰기> 수업모형 및 교수법을 모색하고자 한다. 스포츠마케팅학과에서 <전공 글쓰기>가 필요한 이유는 스포츠마케팅학과의 전문 용어를 숙지한 후 이 용어를 활용하여 학과의 특성을 반영한 전문적인 기획서를 작성할 수 있는 역량을 기르기 위한 것이다. 학과의 특성상 경쟁력 있는 기획서를 쓰는 것을 주된 목적으로 하는 스포츠마케팅학과의 <전공 글쓰기>는 총 16주로 구성되어 있다. 이 과정은 먼저, 본격적인 글쓰기를 시작하기 전의 예비단계로서 손글씨를 통한 심리적 불안감 극복하기, 두 번째, 기획서 만들기의 전단계로서 짧은 글 만들기, 세 번째, 기획서 작성 이론 강의, 네 번째, 기획서 작성 실습의 과정으로 진행되었다. 이처럼 기획서를 작성하는 것을 주목적으로 한 <전공 글쓰기>를 통해 스포츠마케팅학과의 학생들은 스포츠마케팅이라는 전공의 특성을 더욱 뚜렷이 숙지하게 되었으며, 기획서와 제안서 작성에 필요한 지식과 기술을 동시에 습득하는데 매우 큰 도움이 된 것으로 나타난다. 스포츠마케팅학과의 이 사례는 향후 각 학과의 고유의 특성에 맞는 <전공 글쓰기> 강의모형과 교수법을 개발하는 데 많은 시사점을 던져준다는 점에서 상세히 살펴볼 필요가 있다. <Writing in major> is originated from courses in the United States and the United Kingdom. The purpose of <Writing in major> for college freshmen in liberal arts courses is so vague and extensive that it has some limitations in learning discourse developmental methods of major courses. There are four specific reasons to learn <Writing in major>. First, it contributes to the growth in knowledge of a major. Second, it develops academic writing skills by learning characteristics of discourse in major courses. Third, it can help find positions related to students’ majors directly because they have stable identities through those abilities motioned above. Finally, it generates self-expression abilities, creative problem solving abilities, and convergence and integration thinking capabilities that are needed as a specialist at the present day. <Writing in major> was established in four departments of Keimyung University in fall semester, 2013 and twenty eight departments in fall semester, 2014. The purpose of this paper is to research suitable models of instruction and teaching methods examining the cases of <Writing in major> of Sports Marketing students in Keimyung University. The reason that Sports Marketing needs the course <Writing in major> is that students have to have the abilities to write project proposals utilizing jargons in the field of sports marketing. <Writing in major> in Sports Marketing whose purpose is writing project proposals consists of 16 weeks. First process called preliminary stage was composed of overcoming psychological anxiety through handwriting. Writing a short paragraph as a previous step of writing project proposals and learning principles of them were followed. As a final step, students wrote the project proposals. Through <Writing in major>, students in Sports Marketing became well-acquainted with knowledge of their own major and practical skills. This case will henceforward to be a part of developing decent models of instruction and teaching methods in <Writing in major>. KCI Citation Count: 3